EFEKTIVITAS PEMBERIAN JUS BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KADAR HEMOGLOBIN TENAGA MEDIS DI RUMAH SAKIT AMALIA MEDIKA PANGKALAN KERINCI - Situmorang, Nurbaity; Suharsih; Saragih, Yuni Darmawati (Jurnal Biogenerasi, 2023)
Anemia is a common problem that often occurs in developing countries including Indonesia, most anemia is caused by hemoglobin levels less than 11 g/dl. Hemoglobin is a complex protein that binds iron (Fe) and is present in erythrocytes. Low hemoglobin levels are caused by iron deficiency, folic acid deficiency and chronic disease. The increase in hemoglobin levels with iron and vitamin C can be higher than with iron alone. Red dragon fruit (Hylocereus polyrhizus) has long been consumed by the public as a medicine to increase blood. This fruit contains organic acids, protein, minerals such as potassium, magnesium, calcium and iron as well as vitamin C. This study aims to determine the effectivity of giving red dragon fruit juice (Hylocereus polyrhizus) on hemoglobin levels in medical personnel at Amalia Medika Hospital Pangkalan Kerinci. This study used a pre-experimental method with a one group pretest-posttest design, in which hemoglobin levels were measured before giving red dragon fruit juice and after the respondent was given red dragon fruit juice 4 times in 30 days. The results showed that there was a significant difference between hemoglobin levels before and after administration of red dragon fruit juice with p=0.000 (α=0.05) in the paired sample t test. This means that there is an effect of giving dragon fruit juice on the hemoglobin level of medical staff at Amalia Medika Hospital in Pangkalan Kerinci, namely an increase in hemoglobin levels after being given dragon fruit juice of 2.61 g/dL to the respondent.